2017
DOI: 10.1186/s12910-017-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge about biobanking among healthcare students and their willingness to donate biospecimens

Abstract: BackgroundBiobanks and biospecimen collections are becoming a primary means of delivering personalized diagnostics and tailoring individualized therapeutics. This shift towards precision medicine (PM) requires interactions among a variety of stakeholders, including the public, patients, healthcare providers, government, and donors. Very few studies have investigated the role of healthcare students in biobanking and biospecimen donations. The main aims of this study were (1) to evaluate the knowledge of senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 50 publications
12
77
4
Order By: Relevance
“…Our findings are similar to other studies showing about half of people are not familiar with cancer genetic testing (Gammon et al 2011;Mai et al 2014;Quillin et al 2010). Even more patients were unfamiliar with DNA banking; although attitudes about and intentions toward DNA banking were favorable, consistent with prior research (Merdad et al 2017;Quillin et al 2010;Rogith et al 2014). Although most patients had heard something about Angelina Jolie's story of genetic testing, that awareness was not a predictor of accessing genetics services in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar to other studies showing about half of people are not familiar with cancer genetic testing (Gammon et al 2011;Mai et al 2014;Quillin et al 2010). Even more patients were unfamiliar with DNA banking; although attitudes about and intentions toward DNA banking were favorable, consistent with prior research (Merdad et al 2017;Quillin et al 2010;Rogith et al 2014). Although most patients had heard something about Angelina Jolie's story of genetic testing, that awareness was not a predictor of accessing genetics services in this study.…”
Section: Discussionsupporting
confidence: 90%
“…As the patients in our study did not particularly mention the risks they feared, these possibly could be the fear of unknown or of potential side effects. Confidentiality breach was not found to be a major concern as opposed to other studies where misuse of information and doubts regarding randomization were predominant reasons for nonparticipation [7,11,13,15].…”
Section: Discussioncontrasting
confidence: 75%
“…As researchers are faced with the problem of patient participation in research globally, understanding the barriers limiting patients' interests in research is important in designing future research projects that ensure participant satisfaction and recruitment. While extensive work has been done to evaluate Western patients' perspectives, there have been only few studies representing Asian patients' attitude towards research participation, which could be due to lack of patient or physician interest as well as limited funding and infrastructure to promote research [8,9], while various Asian studies have been performed to assess attitudes of healthy subjects or mixed group of patients towards research participation [2,6,[10][11][12][13][14]; to the best of our knowledge, this is the first Asian study on Parkinson patients to understand their attitudes towards clinical research and tissue donation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an Australian study revealed that the majority of health professionals had no knowledge of biobanks [9]. The lack of knowledge about biobanking was also observed among health students in Saudi Arabia [14]. Regarding the association between the knowledge of biobanks and socio-demographic factors, our study demonstrated that participants aged between 25 and 34 years, physicians, and health professionals working at the University Table 4.…”
Section: State Of Knowledge Of Biobanksmentioning
confidence: 56%
“…Italian study among university students, demonstrated that women were more willing to donate their biological samples to biobanks than men, and medical students or professional nursing were more willing to do so than law students [15]. Another study conducted among senior health students in Saudi Arabia, showed that the majority (89%) of the participants were willing to donate biospecimens to biobanks for biomedical research purposes [14].…”
Section: Willingness Of Health Professionals To Donate Biospecimens Tmentioning
confidence: 99%